Mutual information spectrum for selection of event-related spatial components. Application to eloquent motor cortex mapping - Ossadtchi, Alexei; Pronko, Platon; Baillet, Sylvain; Pflieger, Mark; Stroganova, Tatiana A. (Frontiers in Neuroinformatics, 2014)
Spatial component analysis is often used to explore multidimensional time series data whose sources cannot be measured directly. Several methods may be used to decompose the data into a set of spatial components with temporal loadings. Component selection is of crucial importance, and should be supported by objective criteria. In some applications, the use of a well defined component selection criterion may provide for automation of the analysis. In this paper we describe a novel approach for ranking of spatial components calculated from the EEG or MEG data recorded within evoked response paradigm. Our method is called Mutual Information Spectrum and is based on gauging the amount of mutual information of spatial component temporal loadings with a synthetically created reference signal. We also describe the appropriate randomization based statistical assessment scheme that can be used for selection of components with statistically significant amount of mutual information. Using simulated data with realistic trial to trial variations and SNR corresponding to the real recordings we demonstrate the superior performance characteristics of the described mutual information based measure as compared to a more conventionally used power driven gauge. We also demonstrate the application of the Mutual Information Spectrum for the selection of task-related independent components from real MEG data. We show that the Mutual Information spectrum allows to identify task-related components reliably in a consistent fashion, yielding stable results even from a small number of trials. We conclude that the proposed method fits naturally the information driven nature of ICA and can be used for routine and automatic ranking of independent components calculated from the functional neuroimaging data collected within event-related paradigms.